Proceedings of the 13th International Conference on Computational Semantics - Long Papers 2019
DOI: 10.18653/v1/w19-0416
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Explicitate Connectives with Seq2Seq Network for Implicit Discourse Relation Classification

Abstract: Implicit discourse relation classification is one of the most difficult steps in discourse parsing. The difficulty stems from the fact that the coherence relation must be inferred based on the content of the discourse relational arguments. Therefore, an effective encoding of the relational arguments is of crucial importance. We here propose a new model for implicit discourse relation classification, which consists of a classifier, and a sequence-to-sequence model which is trained to generate a representation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
0
20
0
2
Order By: Relevance
“…for the training split of Ji is one short of what has been reported in Shi and Demberg (2019) and also the count obtained by using Qin et al (2017)'s preprocessing code. This is due to a duplicate example with label EXPANSION.ALTERNATIVE, which our preprocessing code does not generate.…”
Section: Discussionmentioning
confidence: 99%
“…for the training split of Ji is one short of what has been reported in Shi and Demberg (2019) and also the count obtained by using Qin et al (2017)'s preprocessing code. This is due to a duplicate example with label EXPANSION.ALTERNATIVE, which our preprocessing code does not generate.…”
Section: Discussionmentioning
confidence: 99%
“…The successful usage of a memory network in Shi and Demberg (2019a) showed that instances that share the same relation have close representations.…”
Section: Unsupervised Methods With Information Retrieval Systemmentioning
confidence: 99%
“…Так, в [Cartoni et al 2013] показано, что переводной эквивалент коннектора может дать дополнительную информацию о его семантике и снять неоднозначность интерпретации в случае полисемичных коннекторов. В [Shi et al 2017: 484] подчёркивается, насколько трудным является распознавание имплицитных ЛСО и что нейронные сети плохо справляются с этой задачей из-за нехватки аннотированных данных. Для решения этой практической проблемы в работе предлагается оригинальный метод использования параллельных корпусов (в данном случае англо-французского корпуса).…”
Section: метод поиска имплицитных лсо в параллельных текстахunclassified
“…Несмотря на то, что изменения контекста при переводе, приводящие к соответствиям типа 2. и 3., могут быть оправданными, мы не рассматриваем их как случаи имплицитных ЛСО. Тем не менее, в [Shi et al 2017: 491] особо отмечается важность исследования контекстов, сходных с теми, которые мы относим к типу 2. Хотя такие контексты 1) не включают никакого коннектора, 2) имеют структуру, не позволяющую его добавить, и 3) могут не рассматриваться как содержащие какое-либо ЛСО, они вызывают появление коннектора в переводе, а потому могут дать новую информацию о механизмах функционирования ЛСО в целом и расширить имеющиеся знания о спектре контекстов, включающих ЛСО.…”
Section: анализ полученных результатовunclassified